Historical and personal representation of Colombian teachers through their lifeline - Betancourth Zambrano, Sonia; Riobamba Jiménez, Oscar David; Alvarez Pabón, Karol Melissa (Informes Psicológicos, 2021)
The present study explores the historical-personal representation through the lifeline of 50 teachers of a municipal educational institution located in the south west of Colombia. It was developed under the parameters of ethnographic research, whereby both positive and negative emerging categories were obtained. The first are related to education, sources of happiness, family life, the type of large and low-income home, reflection and resilience. The second have to do with the non-resolution of problems in childhood and adolescence, situations of the Colombian armed conflict, disputes and family and personal difficulties. Among the findings, it is concluded that the lifeline is a comprehensive tool, allowing people to see their past and its influence in the present, also favoring the development of some unfinished personal difficulties in their lives.
Keywords: Life stories; Learning; Teaching staff; Didactics